PERBANDINGAN KELENGKAPAN PENGISIAN REKAM MEDIS KONVENSIONAL DAN PROTOTIPE INTEGRATED ELECTRONIC SURGICAL REPORT (IESR) - Udiyana, Nyoman Dwi Maha; Darmawan, Ede Surya; Candi, Cicilya (Coping: Community of Publishing in Nursing, 2021)
The utilisation of Electronic Medical Record (EMR) is an implementation of information and communication  technological development in healthcare.  EMR improve quality and documentation of  medical record.   Integrated Electronic Surgical Report (IESR) prototype is  an EMR development that concerned on surgical report fulfillment, allows the surgeon  fullfill an android based  medical record efficiently. This research is mixed method study, using qualitative study to get feedback from the IESR user,  and  a cross sectional analytic study to know  the comparison   of  medical records filling completeness between Integrated Electronic Surgical Report (IESR) and conventional medical records  at Sultan Imanuddin hospital. Secondary data of 31 medical record  sample from medical record department in october until december 2020 was obtained. Bivariate analysis result using  Mann_Whitney test showed p=0.061. There are  few positive aspect including: simplicity , short duration and efficiency in medical record fulfilment using IESR. But there is no significant difference between   IESR prototype utilisation and conventional medical record in  term completeness  fulfilment of surgical ward patients medical record.